Does Local Government Expenditure Lead to Human Development in Indonesia? - Imantria, Benny; Kurnia, Akhmad Syakir (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2024)
Human development has become a national development priority in the vision of Indonesia Emas 2045, but the HDI score shows district-level inequality in increasing local government expenditure. This study aims to identify the effect of local government expenditure realization on HDI. The data used is 508 districts of Indonesia in 2017-2022, and it was analyzed using a panel data regression fixed-effect model. The novelty of this study lies in the local government at the district level and local government expenditure according to function and type classification. The study shows that education expenditure, health expenditure, economic expenditure, employee expenditure, and goods and services expenditure have a significant positive effect on HDI, but capital expenditure has a significant negative effect on HDI. Local governments are expected to understand the dominant role of health expenditure in increasing HDI, increase the budget allocation for economic and capital expenditure, reduce the budget allocation for employee and goods and services, and measure the performance of local government expenditure.